Genome-Wide Analysis of the MADS-Box Gene Family in Holoparasitic Plants (Balanophora subcupularis and Balanophora fungosa var. globosa) - Duan, Kunyu; Fu, Hui; Fang, Dongming; Wang, Kaimeng; Zhang, Wen; Liu, Huan; Sahu, Sunil Kumar; Chen, Xiaoli (Frontiers in Plant Science, 2022)
MADS-box is an important transcription factor family that is involved in the regulation of various stages of plant growth and development, especially flowering regulation and flower development. Being a holoparasitic plant, the body structure of Balanophoraceae has changed dramatically over time, and its vegetative and reproductive organs have been extensively modified, with rudimentary flower organs. Meanwhile, extraordinary gene losses have been identified in holoparasitic plants compared with autotrophs. Our study reveals that the MADS-box gene family contracted sharply in Balanophora subcupularis and Balanophora fungosa var. globosa, and some subfamilies were lost, exhibiting reduced redundancy in both. The genes that functioned in the transition from the vegetative to floral production stages suffered a significant loss, but the ABCE model genes remained intact. We further investigated genes related to flowering regulation in B. subcupularis and B. fungosa var. globosa, vernalization and autonomous ways of regulating flowering time remained comparatively integrated, while genes in photoperiod and circadian clock pathways were almost lost. Convergent gene loss in flowering regulation occurred in Balanophora and another holoparasitic plant Sapria himalayana (Rafflesiaceae). The genome-wide analysis of the MADS-box gene family in Balanophora species provides valuable information for understanding the classification, gene loss pattern, and flowering regulation mechanism of MADS-box gene family in parasitic plants.